Field-dependent viscoelastic properties of graphite-based magnetorheological grease - Nazmi, Nurhazimah; N.A.M. Nasir; Mazlan, Saiful Amri; N. A Nordin; M.A.A Rahman; N. Mohamad; Shair, Ezreen Farina (Penerbit Universiti Malaysia Pahang, 2022)
This paper highlights the effect of graphite on the dynamic viscoelastic properties of magnetorheological grease (MRG). Two types of MRG namely MRG and graphite-MRG, GMRG with 0 wt.% and 10 wt. % of graphite respectively was synthesized by using a mechanical stirrer. The rheological properties of both sample at various magnetic field strength from 0 to 0.603 T was analyzed via rheometer under oscillatory mode with strain ranging from 0.001 to 1% with fixed frequency at 1 Hz for strain sweep and frequency ranging from 0.1 to 80 Hz at a constant strain of 0.01 % for frequency sweep. Based on the result obtained, the value of storage and loss modulus are dependent on the graphite content. A high value of storage modulus was achieved in the GMRG sample at all applied magnetic field strengths within all frequency ranges. These phenomena related to the contribution of graphite to forming the chain structure with CIPs and offered a more stable and stronger structure as compared with MRG. Moreover, the reduction in the value of loss modulus in GMRG was noticed compared to MRG at on-state conditions reflected by the stable structure obtained by GMRG. Lastly, both samples displayed a strong solid-like (elastic) behavior due to the high value of storage modulus, G’ acquired compared to loss modulus, G’’ at all frequency ranges. Therefore, the utilization of graphite in MRG can be used in wide applications such as brake and seismic dampers.